Immunogenicity of pentavalent rotavirus vaccine in Chinese infants. Issue 13 (22nd March 2019) - Mo, Zhaojun; Ma, Xiao; Luo, Peng; Mo, Yi; Kaplan, Susan S.; Shou, Qiong; Zheng, Minghuan; Hille, Darcy A.; Arnold, Beth A.; Liao, Xueyan; ,
Highlights: RotaTeq TM was immunogenic in Chinese infants. RotaTeq TM did not interfere with the immune responses to co-administered tOPV in Chinese infants. RotaTeq TM did not interfere with the immune responses to co-administered DTaP in Chinese infants. Abstract: Background: A phase III, randomized, double-blind, placebo-controlled clinical study was conducted in China to assess the efficacy, safety, and immunogenicity of the pentavalent rotavirus vaccine (RotaTeq TM, RV5) among Chinese infants. The efficacy and safety data have been previously reported. This report presents the immunogenicity data of the study. Methods: 4, 040 infants aged 6–12 weeks were randomly assigned in a 1:1 ratio to receive 3 oral doses of RV5 or placebo. Trivalent oral poliovirus vaccine (tOPV) and diphtheria, tetanus, and acellular pertussis vaccine (DTaP) were administered in a staggered-use (N = 3, 240) or concomitant-use (N = 800) schedule. Immunogenicity of RV5 was evaluated in 800 participants (400 participants from each staggered- and concomitant-use immunogenicity subgroup). Geometric mean titers (GMTs) and seroresponse rates (≥3-fold rise from baseline to PD3) were measured for anti-rotavirus IgA in the staggered- and concomitant-use subgroups and measured for serum neutralizing antibodies (SNAs) to human rotavirus serotypes G1, G2, G3, G4, P1A[8] in the staggered-use subgroup. Immune responses to tOPV and DTaP co-administered with RV5 were also evaluated in the concomitant-use immunogenicity subgroup. (ClinicalTrials.gov registry: NCT02062385) Results: The PD3 GMT and seroresponse rate of anti-rotavirus IgA were higher in the RV5 group (82.42 units/mL, 89.4%) compared to the placebo group (0.33 units/mL, 10.1%). Rotavirus type-specific SNA responses were also higher in the RV5 group compared to the placebo group. In the concomitant-use subgroup, the seroprotection rates of anti-poliovirus type 1, 2, 3 in the participants who received RV5 were non-inferior to those who received placebo, and the antibody responses to DTaP antigens were comparable between the two vaccination groups. Conclusions: RV5 was immunogenic in Chinese infants. Immune responses induced by tOPV and DTaP were not affected by the concomitant use of RV5.